Highly conductive electrodes of graphene oxide/natural rubber latex-based electrodes by using a hyper-branched surfactant. (5th June 2016) - Suriani, A.B.; Nurhafizah, M.D.; Mohamed, A.; Masrom, A.K.; Sahajwalla, V.; Joshi, R.K.
Abstract: A custom-made surfactant called sodium 1, 4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1, 4-dioxobutane-2-sulfonate (TC14) was used to assist the dispersion of graphene oxide/natural rubber latex (GO/NRL) nanocomposites by the one-step method. NRL was intermixed in the electrolyte during the electrochemical exfoliation of the produced GO. The conductivity of the sample was measured by using a four-point probe measurement and was found to be 2.65 × 10 − 4 S cm − 1 . The tri-chain of the hyper-branched TC14 surfactant successfully improved the dispersions and conductivity of the GO/NRL nanocomposite. Cyclic voltammetry was employed to study the supercapacitor performance of the nanocomposite. A high capacitance value of 35 F g − 1 was measured from the sample at a scan rate of 100 mV s − 1 . The use of low-surface-tension triple-tail TC14 can efficiently adsorb and give triple interactions between the GO and NRL matrix. Meanwhile, a close comparison study of available commercial surfactant SDS in the fabrication of GO/NRL nanocomposites was also conducted with a similar preparation method. The conductivity obtained for SDS-GO/NRL nanocomposites was lower, which was found to be 2.59 × 10 − 7 S cm − 1 . Therefore, the introduction of TC14 surfactant can uncover the possibility for the development of low cost, conductive, environmentally friendly, and flexible GO/NRL nanocomposite-based electrode for supercapacitor application. Graphical abstract: Highlights: A new custom-made triple-tail surfactant was introduced into the nanocomposites. The triple-tail surfactant enhanced the homogeneity and electrical conductivity of nanocomposites. Conductive and flexible electrodes have potentials in supercapacitor applications.